2012
DOI: 10.1084/jem.20111512
|View full text |Cite
|
Sign up to set email alerts
|

MYC pathway activation in triple-negative breast cancer is synthetic lethal with CDK inhibition

Abstract: Triple-negative breast cancers with elevated MYC are sensitized to CDK inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
264
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(289 citation statements)
references
References 78 publications
20
264
0
2
Order By: Relevance
“…MTBP protein levels were elevated in all of the TNBC cells (Fig 2C). In comparison, the oncogenic transcription factor MYC, which has previously been shown to positively regulate MTBP expression and to be elevated in aggressive breast cancers, was also elevated in these same cells (12, 24). Therefore, MTBP mRNA levels are the highest in patient samples of the clinically aggressive TNBC subtype, and TNBC cell lines have high levels of MTBP mRNA and protein.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…MTBP protein levels were elevated in all of the TNBC cells (Fig 2C). In comparison, the oncogenic transcription factor MYC, which has previously been shown to positively regulate MTBP expression and to be elevated in aggressive breast cancers, was also elevated in these same cells (12, 24). Therefore, MTBP mRNA levels are the highest in patient samples of the clinically aggressive TNBC subtype, and TNBC cell lines have high levels of MTBP mRNA and protein.…”
Section: Resultsmentioning
confidence: 74%
“…TNBCs are reported to have a higher proliferative index when compared to receptor positive high-grade invasive carcinomas (29). In addition, elevated MYC transcriptional activity, which is correlated with decreased breast cancer patient survival, is linked to increased proliferation in breast cancer, and the TNBC subtype has the highest MYC transcriptional activity (24). We recently determined patients with breast cancers that express high levels of both MYC and MTBP have a worse prognosis than those with just high MYC expression (13), suggesting cooperation between MYC and MTBP overexpression in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies show that cell cycle regulation is an attractive target in cancer therapy, especially in gliomas [29, 30]. Cell cycle arrest triggers tumour senescence and prevents tumour progression and have not any obvious effects on normal tissues, which may be related to the inhibition of regulators such as CDK1, D-type cyclins, CDK4 and CDK6[31, 32]. Our data showed that isogambogenic acid led to cell cycle arrest in human glioma U87 and U251 cells, so this drug has a good toxicity against gliomas and may have a low toxicity in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of level I evidence, the matching of patients to clinical trials of drugs that are likely to target each patient’s specific tumor’s molecular aberrations holds significant promise. Moreover, alterations that we did not consider actionable in this analysis may be sensitive to certain targeted therapeutics (eg, MYC and CDK inhibitors), and novel therapies directed at other targets such as TP53 are rapidly evolving (20). …”
Section: Discussionmentioning
confidence: 99%